Climate Change Impact and Sustainable Adaptation Strategies for Climate-Resilient Paddy Cultivation in Chandrapur District, Central India (Mongolian Journal of Agricultural Sciences, 2023)
Agriculture is the principal sector of the Indian economy. Rice paddies are a temperature-sensitive crop and require a sufficient quantity of water for cultivation. The study's objective is to observe, assess, and develop adaption techniques for farmers who are marginalized in Chandrapur district, central India, through the practice of paddy cultivation. For this purpose, 70 marginalized farmers were identified from the eight villages of the district. The information from this group of farmers was gathered using a custom-created, and field-tested questionnaire. The major climate change impact on various paddy growth stages and livestock were identified as soil fertility reduced (94.28%), high temperature reduced paddy growth (88.56%), predominance of insects and pests increased to 98.57%, and new pest and bug species are impacting paddy (86.14%), paddy quality deteriorated at the time of harvest (92.85%), heatstroke in livestock engaged in paddy cultivation (100%) etc. To increase this group of marginalized farmers' capacity for resilience, climate-smart agriculture strategies for various paddy growth stages have been identified from the scientific and technical literature and discussed in this document. These strategies include village seed bank, dryland zero tillage, modified rice intensification system and rice drum seeding, community paddy nursery, use of composite varieties, micro dams, irrigation scheduling, paddy-fish agriculture system, designing of free stall barn etc. In addition to these strategies, other support mechanisms such as national-level policy, financial provision, institutional mechanism, capacity development and improvement will transform from subsistence farming to sustainable farming and lead to sustainable livelihood.